"Come be off with you": White spatial control in the representation of Aboriginality in early Australian drama. (June 2017) - Miller, Benjamin
Scholars of early Australian drama have over-emphasized the stylistic relationship between Aboriginal characters in early Australian drama and blackface characters in early American drama. Focusing on stylistic connections between early US and Australian theatre potentially overlooks the complex ideological similarities in representations of race on the American and Australian stage. This article provides a close reading of two of Australia's first plays — David Burn's "The Bushrangers" and Henry Melville's "The Bushrangers; or, Norwood Vale" — in order to nuance the critical record exploring the influence of American drama on Australian drama around 1830. Looking beyond formal connections between early US and Australian theatre can reveal an ideology of white spatial control underpinning early representations of Aboriginality and blackness in Australian and American drama.